2018
DOI: 10.1002/jcb.26600
|View full text |Cite
|
Sign up to set email alerts
|

IL‐1β‐induced miR‐34a up‐regulation inhibits Cyr61 to modulate osteoarthritis chondrocyte proliferation through ADAMTS‐4

Abstract: Osteoarthritis (OA) is the most prevalent degenerative joint disease with multifactorial etiology caused by risk factors. The degradation of aggrecan by upregulated ADAMTS (a disintegrin and metalloproteinase with thrombospondin motifs) is the key event in the development of OA. ADAMTS-4 contributes to aggrecan degradation in human OA. Cysteine-rich angiogenic inducer 61 (Cyr61), which is associated with diseases related to chronic inflammation, is found in articular cartilage from patients with osteoarthritis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 50 publications
1
14
0
Order By: Relevance
“…Additionally, miR-34a expression was induced by IL-1β in OA [31]. Consistent with previous studies [35], we found that The mRNA a and protein b expression of SYVN1 was detected in OA cells (IL-1β) transfected with anti-NC, anti-miR-34a-5p, anti-miR-34a-5p + scramble and anti-miR-34a-5p + siSYVN1 by qRT-PCR and western blot. c Cell proliferation was measured in OA cells (IL-1β) transfected with anti-NC, anti-miR-34a-5p, anti-miR-34a-5p + scramble and anti-miR-34a-5p + siSYVN1 after transfection 24 h, 48 h, 72 h by MTT assay.…”
Section: Discussionsupporting
confidence: 91%
“…Additionally, miR-34a expression was induced by IL-1β in OA [31]. Consistent with previous studies [35], we found that The mRNA a and protein b expression of SYVN1 was detected in OA cells (IL-1β) transfected with anti-NC, anti-miR-34a-5p, anti-miR-34a-5p + scramble and anti-miR-34a-5p + siSYVN1 by qRT-PCR and western blot. c Cell proliferation was measured in OA cells (IL-1β) transfected with anti-NC, anti-miR-34a-5p, anti-miR-34a-5p + scramble and anti-miR-34a-5p + siSYVN1 after transfection 24 h, 48 h, 72 h by MTT assay.…”
Section: Discussionsupporting
confidence: 91%
“…Both miR-34a and miR-34b are upregulated in human knee OA AC compared to normal AC [ 147 , 181 ]. Also primary cell cultures of human knee OA AC show increased miR-34a expression compared to healthy controls [ 182 ].…”
Section: Mirna Regulation Of Fibroblast Growth Factor 2 Transformmentioning
confidence: 99%
“…Another target is cysteine-rich angiogenic inducer 61 ( CYR61 ), which inhibits ADAMTS-4. Indeed, upregulation of miR-34a by rIL-1β promotes ADAMTS-4 expression in human AC cells [ 181 ]. In human primary immortalized fibroblasts the MAPK activated transcription factor ELK1 is involved in miR-34a expression [ 183 ].…”
Section: Mirna Regulation Of Fibroblast Growth Factor 2 Transformmentioning
confidence: 99%
“…The prevalence of OA worldwide is staggeringly high with an estimated over 250 million people affected and with a lifetime risk for worsening to knee OA of approximately 40% [3]. Chondrocyte, a primary cell type of articular cartilage which occupies approximately 1% of total cartilage volume, is essential for retaining the dynamic equilibrium between catabolism and anabolism of the extracellular matrix in articular cartilage and has been deemed as one of the indispensable regulators of OA pathogenesis [4,5]. Declining cell number and cell viability of chondrocytes is implicated in the progression and advancement of OA [6].…”
Section: Introductionmentioning
confidence: 99%